Pedagogic Competencies of PPL Teachers In ‎Madura: ‎ An Analysis of Tutors and Students’ Perceptions - Abd. Mukhid, (TADRIS: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to find out two things, namely how (a) the perception of civil servant teachers and (b) students' perceptions of the pedagogic competence of PPL teachers in schools. This study uses a descriptive type of quantitative approach. The research subjects consisted of 15 civil servant teachers and 237 students, 24 PPL teachers, and 4 schools/madrasahs, following the provisions of the 10% random sampling technique from Arikunto. The results showed that (a) the PPL teacher's pedagogic competence based on the perception of the civil servant teacher was classified as good. This is evidenced by the value of 73% of respondents' answers (H0 is rejected) (b) PPL teacher's pedagogic competence based on students' perceptions is quite adequate. This is evidenced by the value of 69.83% of the respondents' answers. (H0 is rejected). Based on the research findings, it is hoped that (a) civil servant teachers can provide more optimal guidance to student practitioners regarding lesson plans, discipline, order, and others; (b) students are expected to pay more attention to and optimize their potential when participating in learning with PPL teachers, (c) practical students as PPL teachers are expected to better master the characteristics of students, learning theories, better prepared in preparing lesson plans, better able in carry out educational learning, are better able to develop the potential of students, are better able to communicate effectively and politely, are better able to carry out and use evaluations, and are reflective.